Effects of laughter yoga practiced by the first year nursing students before clinical practice on their perceptions of stress and meaning of life: a randomized controlled trial - Kıvan Çevik Kaya; Çiğdem Gamze Özkan; Derya Ağiş (BMC Nursing)
Abstract Background Laughter yoga has a positive effect on the person’s mental/general health, life satisfaction and psychological well-being and enables the person to cope with stress. Objective This randomized controlled study was conducted to determine the effect of laughter yoga practiced by first year nursing students before clinical practice on their perceptions of stress and meaning of life. Method In this experimental randomized and controlled study including a control group, we administered a pre-test, post-test one and post-test two to the participating students. Ninety nursing students who met the inclusion criteria comprised the study sample. The students in the intervention group took part in eight sessions of laughter yoga for four weeks, twice a week. The Descriptive Information Form, Perceived Stress Scale, and Meaning and Purpose of Life Scale were administered to collect the study data. Results The mean age of the students in the intervention and control groups was 19.65 ± 2.27 and 19.18 ± 1.01 years, respectively. Of the participants in both groups, 91.1% were women, and 97.8% were single. The difference between the mean scores obtained from the Perceived Stress Scale and the Meaning and Purpose of Life Scale by the students in the intervention group at the pre- and posttest were statistically significant (p < 0.05). Conclusion Laughter yoga positively affects nursing students’ perceptions of stress and meaning and purpose of life. Trial registration Trial Registration number and Date of registration: NCT06042959 / 09/14/2023 06:17.